Collaborative Governance Desa Pancasila: Implementasi Nilai-Nilai Toleransi dalam Aktualisasi Pemerintahan Desa - Dinda Amalia Putri (Fakultas Ilmu Sosial dan Ilmu Politik, 2026)
This study examines the implementation of collaborative governance processes in Pancasila villages and the values of tolerance in the actualization of village government in Sukoreno Village, Umbulsari District, Jember Regency, as a Pancasila Village. The background of this research is based on the importance of implementing tolerance values in a pluralistic society and the need for the involvement of various aktors in implementing inclusive and participatory village governance. The purpose of this study is to analyze the collaborative process between aktors and their respective roles. This study uses a qualitative, descriptive approach. Data collection techniques were conducted through interviews, observation, and documentation. Informant selection was conducted purposively, selecting informants with knowledge, experience, and direct involvement in the collaborative process, such as the village government, the Badan Permusyawaratan Desa (BPD), religious leaders, and the Kerukunan Umat Beragama (KUB). Data analysis was conducted using the Miles and Huberman interdisciplinary model, which includes data reduction, data presentation, and conclusion drawing. This study utilizes the collaborative governance theory of Ansel and Gash (2008). The research results show that the collaborative governance process operates through five main indicators: face-to-face dialogue, trust-building, commitment to the process, shared understanding, and intermediate outcomes. The study concludes that collaborative governance plays a crucial role in implementing the values of tolerance, thereby creating a harmonious, inclusive village government based on Pancasila values.
:: Finalisasi file repositori 20 Juli 2026_Kurnadi
Keywords: Collaborative Governance; Tolerance; Pancasila Village; Village Government